“Bajka o Bajalicаma” or the Dragon in the Age of ‘Inter-’ (Intertextuality, Intermediality, Interculturality, Internet) - Paser Ilić, Snežana D. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The paper studies the first literary work for children by Vojislav Todorović, the novel Bajka o Bajalicаma (The Fairy Tale of Bajalice). The work is analysed on the level of intertextuality, since it carries direct allusions to characters and motifs from popular works for children. By means of in-depth examination of the author’s poetics, we come to the conclusion that this complex achievement blends elements of the miraculous, folklore, and original authorship within both domestic and international literary traditions. Special attention is given to the relationship between folklore elements and their transformation within this literary work. The realistic framework, which anchors the world of the miraculous, plays a crucial role in engaging the target reader—the modern child.